2014
DOI: 10.2215/cjn.08940813
|View full text |Cite
|
Sign up to set email alerts
|

Renal Relevant Radiology

Abstract: SummaryAutosomal-dominant polycystic kidney disease is a systemic disorder and the most common hereditary renal disease, which is characterized by cyst growth, progressive renal enlargement, and development of renal failure. The cystic nature of autosomal dominant polycystic kidney disease and its renal and extrarenal complications (kidney stones, cyst hemorrhage, intracerebral aneurysm, liver cysts, cardiac valve abnormalities, etc.) give radiologic imaging studies a central role in the management of these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 52 publications
0
37
0
1
Order By: Relevance
“…Furthermore, HtTKV serves as a better predictor than baseline age, serum creatinine, BUN, urinary albumin, or monocyte chemotactic protein-1 excretion for the onset of renal insufficiency (25,26). (11,16,44).…”
Section: Analyses Of Abdominal Magnetic Resonance Imagingmentioning
confidence: 99%
“…Furthermore, HtTKV serves as a better predictor than baseline age, serum creatinine, BUN, urinary albumin, or monocyte chemotactic protein-1 excretion for the onset of renal insufficiency (25,26). (11,16,44).…”
Section: Analyses Of Abdominal Magnetic Resonance Imagingmentioning
confidence: 99%
“…Hypertension is common in ADPKD; between 31% of affected women and 46% of affected men are hypertensive by age 40 years, and 50%-60% of patients are hypertensive, despite normal renal function (12,13). These data underscore the relevance of the disease itself, not the presence of reduced GFR as the key mediator of hypertension, and suggest that vascular abnormalities in ADPKD may be responsible for this early hypertensive phenotype.…”
Section: Pathogenesis Of Hypertension In Early Pkd: Clinical Implicatmentioning
confidence: 87%
“…Intracystic bleeding is a potential complication of cysts and is part of the differential diagnosis of a cyst infection [18,23] . However, the panel concluded that it is not necessary to exclude a cyst bleeding to diagnose cyst infection and therefore should not be included as diagnostic criterion.…”
Section: Discussionmentioning
confidence: 99%